Effects of Prosopis farcta Root Extract in the Vascular Reactivity of Isolated Goat Coronary Artery - Rasheed, Rezhna Adil; Salih Ibrahim Kakey, Ismail (Kurdistan Journal of Applied Research, 2019)
Prosopis species is a medicinal plant, well-known for its beneficial effects in treating various smooth muscles disorders, and its phytochemical analysis revealed the presence of different bioactive compounds in different parts of the plant, most of which show a great role in reducing cardiovascular risks. In the present study, the cardiovascular effect of Prosopis farcta Root Extract (PFRE) was investigated in vitro for possible mechanisms of the extract effect in the vascular reactivity of isolated goat coronary artery (CA) using Organ bath and PowerLab Data Acquisition system. The results of the recording and analyzing of the effect of the PFRE in isolated CA, showed the negative inotropic activity of the extract in CA rings with intact-endothelium, while in CA ring with hyperglycemic-induced endothelium dysfunction the extract tended to vasodilate the CA ring non-significantly, and the extract induced dose-dependent vasodilation in CA rings pre-constricted with high concentration of (30 mM)KCl and showed no effects on contractions induced by (1X10-3-1X10-5) Phenylephrine PE, which is an indicator for its blockade activity on L-type voltage-dependent Ca+2 channel and non-interfering of the extract with the receptor-operated Ca+2 channel. The mechanical recording of the CA ring activities, revealed different potassium (K+) channels including selective calcium-activated potassium channel, ATP-sensitive potassium channel, and different endothelium-derived relaxing factors (EDRF) including nitric oxide and Prostacyclin (PGI2 ) seems to have no role in the relaxation effects of the extract, while the endothelium derived-hyperpolarizing factor (EDHF); epoxy eicosatrienoic acid (EET) showed significant participation in the vasodilation effects of the extract. On the other hand, the extract tended to relax the CA rings through its antagonizing of Ca+2, reducing and inhibiting Ca+2 influx and release from internal stores and interfering with the voltage-operated Ca+2 channels through its alkaloid and flavonoid active compounds which suggested to be the most predicted mechanisms for the maintenance of vasodilating tone and coronary circulation of the PFRE in coronary artery.